Nanoparticle-Based Bioaffinity Assays: From the Research Laboratory to the Market - Farka, Zdeněk; Brandmeier, Julian C; Mickert, Matthias J; Pastucha, Matěj; Lacina, Karel; Skládal, Petr; Soukka, Tero; Gorris, Hans H (Advanced materials (Deerfield Beach, Fla.), 2024)
Advances in the development of new biorecognition elements, nanoparticle-based labels as well as instrumentation have inspired the design of new bioaffinity assays. This review critically discusses the potential of nanoparticles to replace current enzymatic or molecular labels in immunoassays and other bioaffinity assays. Successful implementations of nanoparticles in commercial assays and the need for rapid tests incorporating nanoparticles in different roles such as capture support, signal generation elements, and signal amplification systems are highlighted. The limited number of nanoparticles applied in current commercial assays can be explained by challenges associated with the analysis of real samples (e.g., blood, urine, or nasal swabs) that are difficult to resolve, particularly if the same performance can be achieved more easily by conventional labels. Lateral flow assays that are based on the visual detection of the red-colored line formed by colloidal gold are a notable exception, exemplified by SARS-CoV-2 rapid antigen tests that have moved from initial laboratory testing to widespread market adaption in less than two years.
Keywords: Covid-19; biosensor; digital assay; Nanoparticles; senzitivita a specificita; Sensitivity and Specificity; immunoassay; point-of-care testing; nanoparticle; imunoanalýza; Immunoassay; nanočástice